Adversity Quotient and Future Orientation of Adolescents at LPKA Class II Bandar Lampung - Muslimah; Meilia Ishar; Tansri Adzlan Syah; MUSLIMAH, MUSLIMAH (Psikoislamedia: Jurnal Psikologi, 2025)
Adolescents serving time in LPKA face psychological pressure in the form of low self-esteem and pessimism that can hinder future orientation. Adversity quotient, the ability to face and overcome difficulties, is believed to play an important role in shaping a positive future direction. This study aims to analyze the relationship between adversity quotient and future orientation in 40 adolescents aged 18-21 years in LPKA Class II Bandar Lampung. The method used was quantitative correlation with data collection through the future orientation scale (Nurmi, 1991) and the adversity quotient scale (Stoltz, 2000). The analysis used Spearman's rank correlation test because the data were not normally distributed. Results showed a significant positive relationship between adversity quotient and future orientation (r = 0.616; p < 0.05), so the hypothesis was accepted. This finding confirms the novelty of the study by highlighting the importance of psychological factors in the rehabilitation of juveniles with legal problems, as well as its practical implications in the design of coaching programs based on increasing adversity quotient.  Keywords: Adversity Quotient, Future Orientation, Children's Special Development Institution